Analisis Sistem Peradilan Pidana Anak (SPPA) untuk Penegakan Hukum Pidana Kejahatan Klitih Wilayah Bantul - Ilyas Elfansyah (International Forum of Researchers and Lecturers, 2026)
The phenomenon of street violence known as klitih in Bantul Regency predominantly involves juveniles and has become a serious public concern due to its impact on community safety and public order. This condition creates a dilemma in criminal law enforcement because juvenile offenders must remain protected under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA). This study aims to analyze the application of criminal law to juvenile offenders involved in klitih based on the Juvenile Criminal Justice System and to identify the obstacles encountered by law enforcement officers in handling such cases in Bantul Regency. The research employed normative and empirical juridical methods with a descriptive-analytical approach. Data were collected through library research, interviews, observations, and documentation, and subsequently analyzed using qualitative methods. The findings indicate that law enforcement against juvenile klitih offenders has emphasized the principles of child protection, restorative justice, and diversion in accordance with the SPPA framework. However, the implementation of these principles has not been fully effective due to resistance from victims and the community, weak parental supervision, negative peer influences, and insufficient coordination among related institutions. Strengthening inter-agency collaboration, improving family involvement, and enhancing public understanding of restorative justice are essential to optimize the implementation of the Juvenile Criminal Justice System in addressing juvenile klitih cases.